C-Reactive Protein to Albumin Ratio for Predicting Coronary Artery Lesions and Intravenous Immunoglobulin Resistance in Kawasaki Disease - Tsai, Chih-Min; Yu, Hong-Ren; Tang, Kuo-Shu; Huang, Ying-Hsien; Kuo, Ho-Chang (Frontiers in Pediatrics, 2020)
Background: C-reactive protein (CRP) to albumin ratio (CRP/Alb) has emerged as a novel marker of inflammation, but few studies have evaluated the role of CRP/Alb ratio in Kawasaki disease (KD). Coronary artery lesions (CAL) in children with KD is a major acquired heart disease. We aimed to assess the association between CRP/Alb ratio and CAL formation in children with KD. Methods: This retrospective study enrolled children diagnosed with KD and divided them into two groups, KD with CAL and KD without CAL. We compared the difference in gender, age, laboratory data, intravenous immunoglobulin (IVIG) resistance rate, and incidence of CAL between the two groups. Multivariable logistic regression analysis was used to assess the independent risk factors of CAL. We adopted receiver operating characteristic (ROC) curve analysis to determine the predictive ability of CRP/Alb ratio in predicting CAL. Results: In total, 410 KD patients were reviewed, with 143 in the KD with CAL group and 267 in the KD without CAL group. KD children with CAL had a higher CRP/Alb ratio than those without CAL (3.14 ± 3.17 vs. 2.12 ± 2.04, p<0.001). Multivariable logistic regression analysis demonstrated that male gender (OR=3.222, p<0.001), incomplete KD (OR=1.968, p=0.031), greater platelet count (OR=1.004, p<0.001), higher CRP (OR=0.982, p=0.048), and higher CRP/Alb ratio (OR=1.994, P=0.016) were all independent risk factors for predicting CAL. KD children with a high CRP/Alb ratio (≥2.94) had a higher incidence rate of CAL and IVIG resistance than those with a low CRP/Alb ratio (<2.94) (49.6% vs. 28.7%, p<0.001 and 11.6% vs. 3.5%, p=0.001, respectively). Conclusions: This report is the first to show the role of CRP/Alb ratio in KD children. CRP/Alb ratio can serve as a novel predicting marker for CAL formation and IVIG resistance in KD.